Ekspektasi Manfaat Ekonomi terhadap Minat Berpolitik dalam Pemilu - Notolegowo, Hantoro Ksaid; Rahmatullah, Sri (CV RIFAINSTITUT, 2024)
Economic expectations are believed to be one of the factors that can influence a person's political decisions. Where voting support is cast will be determined by the extent to which future economic conditions can meet voter expectations. This study aims to analyze the role of expectations of economic benefits on political interest in elections. Elections in this context are specific to the election of president and vice president of Indonesia in 2024. The research method used is quantitative through distributing questionnaires. The results of research on 45 respondents showed that economic policies in the form of advancing the creative economy, implementing a minimum wage that is fair and in accordance with regional conditions, and strengthening the Farming Business Credit program, are the policies most expected by the community, which also makes people very enthusiastic in choosing. These findings can serve as input for presidential and vice presidential candidates to pay more attention to the creative economy, improving wages and providing assistance to farmers.